A mixed microscopic method for differentiating seven species of "Bixie"‐related Chinese Materia Medica. Issue 1 (14th November 2013) - Tang, Yina; He, Xicheng; Quanlan, Chen; Lanlan, Fan; Jianye, Zhang; Zhongzhen, Zhao; Dong, Lisha; Zhitao, Liang; Yi, Tao; Chen, Hubiao
ABSTRACT Confusion in the species associated with the name of "Bixie" in Chinese Materia Medica began centuries ago. In recent decades, diverse medicinal plants from the genera Dioscorea and Smilax, and even minor species from the genus Heterosmilax, have been documented under the name Bixie or a very similar name as folk medicines in different areas of China. However, the traditional efficacies and chemical profiles of these herbs are not exactly the same and even vary wildly. Comprehensive authentication of multiple Bixie herbs has not yet been attempted. To differentiate and ensure the correct use of these Bixie‐related herbs, in this study, seven sorts of representative Bixie herbs (Dioscorea collettii, D. zingiberensis, D. nipponica, D. septemloba, Smilax china, S. glabra, and Heterosmilax japonica) were characterized based on the microscopic examination of their powders and cryotomed transverse sections. This is not only the first attempt to distinguish Bixie herbs by a comprehensive microscopic techniques, including common light microscopy, fluorescence microscopy, and polarized light microscopy, but also it is the first research to observe characteristics of transections of crude drugs under polarized lighting for the purpose of authentication. Polarized light has been found to provide a number of unique characteristics. The results indicate that starch granules, stone cells, vascular bundles, and other significant tissue features can be used to authenticate "Bixie" herbs. The method was proven to be quick, handy, specific, and simple. It should be widely applicable to other herbal materials. Microsc. Res. Tech. 77:57–70, 2014. © 2013 Wiley Periodicals, Inc.